EDUCATIONAL AND METHODICAL COMPLEX OF CHAIR IN CHEMISTRY - Nikolay F. Stas (Высшее образование в России)
The article differentiates the concept of an educational data set for a separate educational program and the concept of an educational and methodical complex of a chair. The contents of available educational complexes in chemistry is considered. The article analyzes the reasons of complexes lack and the conditions for their development. The purpose and the conceptual basis of a complex in the general and inorganic chemistry are offered. The structure and the contents of the educational complex in chemistry developed at Tomsk Polytechnic University are described, its role in educational process is shown.